Prevalence and burden of Toxoplasma gondii infection in HIV-infected people: a systematic review and meta-analysis. Issue 4 (April 2017) - Wang, Ze-Dong; Wang, Shu-Chao; Liu, Huan-Huan; Ma, Hong-Yu; Li, Zhong-Yu; Wei, Feng; Zhu, Xing-Quan; Liu, Quan
Summary: Background: Worldwide, 30% of the world's population have antibodies to the intracellular protozoan parasite Toxoplasma gondii and about 36·7 million people are infected with HIV, but little is known about the prevalence of co-infection with T gondii and HIV. We aimed to characterise the epidemiology and burden of T gondii co-infection in people with HIV infection. Methods: In this systematic review and meta-analysis, we searched PubMed, Embase, Google Scholar, ScienceDirect, Chinese Web of Knowledge, Wanfang, and Chongqing VIP databases for studies reporting T gondii infection in HIV-infected people from inception to Feb 29, 2016. Studies were included if they investigated people with HIV infection and presented data that allowed us to establish the prevalence of T gondii infection. We excluded reviews, repeated studies, or animal studies, as well as studies that provided the final results without raw data, had a sample size less than 30 people, had unclear diagnostic methods of T gondii infection, or that included populations with increased risk of T gondii infection. We extracted the numbers of patients with HIV infection and T gondii co-infection from the identified studies. We estimated pooled prevalence of T gondii infection in HIV-infected people by a random-effects model, and evaluated its overall infection burden worldwide. Findings: Our search identified 7843 records and after removal of duplicates and initial screening, we reviewed 312 studies in full. Of these articles, 238 were excluded, leaving 74 studies that included 25 989 HIV-infected people from 34 countries. Of these people, 7326 had T gondii co-infection and we estimated the pooled worldwide prevalence of T gondii infection to be 35·8% (95% CI 30·8–40·7). 2353 of 8837 of people in Asia and the Pacific had co-infection with T gondii and HIV (prevalence 25·1%, 95% CI 19·0–31·2), and prevalence was low in this region compared with that in sub-Saharan Africa (44·9%, 32·3–57·5, 2129/5686; odds ratio [OR] 0·61), Latin America and the Caribbean (49·1%, 27·9–70·4, 510/980; OR 0·33), and North Africa and the Middle East (60·7%, 24·1–97·3, 245/439; OR 0·29). 1561 of 3780 people in low-income countries had co-infection (54·7%, 95% CI 35·8–73·5), which was higher than in middle-income countries (34·2%, 27·4–40·9, 3632/11 540; OR 1·53) and high-income countries (26·3%, 20·4–32·2, 2133/10 669; OR 2·82). Worldwide, we calculated that there were roughly 13 138 600 (95% CI 11 303 600–14 936 900) cases of T gondii co-infection in HIV-infected people, with 87·1% in sub-Saharan Africa (11 449 500 cases, 95% CI 8 236 500–14 662 500). Interpretation: Our findings suggest that people with HIV infection have a very high burden of T gondii infection, especially in sub-Saharan Africa, and emphasise the importance of routine surveillance for T gondii infection in all HIV-infected people. Funding: National Natural Science Foundation and the Special Fund for Agro-scientific Research in the Public Interest in China.